Carcass and lamb quality from agro-pastoral system in the Middle Atlas (Morocco) - Boughalmi A.; Araba A.; Chatibi S.; Yessef M. (Forage resources and ecosystem services provided by Mountain and Mediterranean grasslands and rangelands, 2014)
In Moroccan Middle Atlas and its foothills sheep farming based on Timahdite breed and on the deliberate combination of the various components of the agro-pastoral system. From spring to early fall, feeding of weaned animals and early pregnant females is based exclusively on pasture. It yields carcasses and meat increasingly appreciated by consumers. In order to study the quality of these products, 3 groups of lambs received 3 different rations, were monitored for 3 months. Five animals from each group were slaughtered to study carcass and meat quality. The study of carcass concerned conformation and fatness, using measurements and European grids. Meat quality evaluation concerned the instrumental study of color, according to CIE L*a*b*model, ultimate pH, and sensory parameters with a taste panel. Preliminary results show that animals fed mainly on concentrate feed had better carcass yield, conformation and fatness than those raised on pastoral resources. Lightness of the meat and yellowness of the subcutaneous fat were higher for lambs raised in the extensive system than animals from intensive farming system. They have lower pH and more preferred by the consumer than that from concentrate and hay based-diet animals.
Joint Meeting of the "Mountain Pastures, Mediterranean Forage Resources (FAO/ESCORENA-CIHEAM) and Mountain Cheese" Network, 2014/06/24-26, Clermont-Ferrand (France)